Regulatory effect of PGE2 on microbicidal activity and inflammatory cytokines in canine leishmaniasis - Venturin, Gabriela Lovizutto [UNESP]; Bragato, Jaqueline Poleto [UNESP]; Melo, Larissa Martins [UNESP]; Rebech, Gabriela Torres [UNESP]; Costa, Sidnei Ferro [UNESP]; de Siqueira, Carlos Eduardo [UNESP]; Oliveira dos Santos Maciel, Marilene [UNESP]; Eugênio, Flávia de Rezende [UNESP]; Patto Santos, Paulo Sérgio [UNESP]; de Lima, Valéria Marçal Felix [UNESP] (Wiley, 2020)
Canine leishmaniasis (CanL) is caused by the intracellular parasite Leishmania infantum. Prostaglandin E2 (PGE2) exerts potent regulatory effects on the immune system in experimental model Leishmania infection, but this influence has not yet been studied in CanL. In this study, PGE2 and PGE2 receptor levels and the regulatory effect of PGE2 on arginase activity, NO2, IL-10, IL-17, IFN-γ, TNF-α and parasite load were evaluated in cultures of splenic leucocytes obtained from dogs with CanL in the presence of agonists and inhibitors. Our results showed that splenic leucocytes from dogs with CanL had lower EP2 receptor levels than those of splenic leucocytes from healthy animals. We observed that NO2 levels decreased when the cells were treated with a PGE2 receptor agonist (EP1/EP2/EP3) or COX-2 inhibitor (NS-398) and that TNF-α, IL-17 and IFN-γ cytokine levels decreased when the cells were treated with a PGE2 receptor agonist (EP2) or PGE2 itself. The parasite load in splenic leucocyte cell cultures from dogs with CanL decreased after stimulation of the cells with PGE2. We conclude that Leishmania infection of dogs modulates PGE2 receptors and speculate that the binding of PGE2 to its receptors may activate the microbicidal capacity of cells.
Keywords: dogs; Leishmania spp.; prostaglandin E2; receptors